2020
DOI: 10.1002/suco.201900380
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of recycled aggregate concrete with chemical admixture

Abstract: Rapid growth in construction has resulted in usage of large quantity of natural resources leading to the degradation of environment. Also, the demolition waste is on the rise year by year due to ending of service of the building and modifications to meet latest requirements. Adoption of technology for recycling the construction and demolition (C and D) waste provides a better way of resolving this issue and it will lead to environmental sustainability. Recycled Concrete Aggregate (RCA) is one such environment‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The stress-strain curve, fracture energy and fracture distribution were analyzed and it was reported that the base force element method (BFEM) can be applied to study the failure mechanisms in heterogeneous materials, such as RAC. Kannan et al 24 studied the effect of chemical admixtures on the mechanical properties and durability of RAC and reported that the addition of chemical admixtures improved the properties of RAC.…”
Section: Introductionmentioning
confidence: 99%
“…The stress-strain curve, fracture energy and fracture distribution were analyzed and it was reported that the base force element method (BFEM) can be applied to study the failure mechanisms in heterogeneous materials, such as RAC. Kannan et al 24 studied the effect of chemical admixtures on the mechanical properties and durability of RAC and reported that the addition of chemical admixtures improved the properties of RAC.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were conducted on the behavior of concretes containing RCA (e.g., References 10–17). As was mentioned in literature, mechanical strength and durability characteristics of concretes having RCA were generally inferior in comparison with those without RCA 18,19 . This is attributed to the poor quality of RCAs owing to the porous nature of the attached mortar, resulting in their lower mechanical strength and durability‐related properties 20 .…”
Section: Introductionmentioning
confidence: 88%
“…The indexes of highperformance concrete are often better than those of ordinary concrete. [36][37][38][39][40][41] Therefore, if the high-performance concrete is used to column, earthquake damage to the column will be greatly reduced. Taking the workshop column and the plaster layer as an example, the detail categories and the corresponding detail seismic damage descriptions are shown in Table 1.…”
Section: The Components and The Detail Seismic Damagementioning
confidence: 99%
“…In general, the column is made of normal concrete rather than high‐performance concrete. The indexes of high‐performance concrete are often better than those of ordinary concrete 36–41 . Therefore, if the high‐performance concrete is used to column, earthquake damage to the column will be greatly reduced.…”
Section: The Determination Of the Components And The Detail Seismic Dmentioning
confidence: 99%